2016
DOI: 10.3171/2015.7.spine15441
|View full text |Cite
|
Sign up to set email alerts
|

Economic value of treating lumbar disc herniation in Brazil

Abstract: OBJECT Lumbar discectomy is one of the most common surgical spine procedures. In order to understand the value of this surgical care, it is important to understand the costs to the health care system and patient for good results. The objective of this study was to evaluate for the first time the cost-effectiveness of spine surgery in Latin America for lumbar discectomy in terms of cost per quality-adjusted life year (QALY) gained for patients in Brazil. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Although RCTs that focus on clinical outcomes can provide robust recommendations for spinal clinical practice [ 22 , 23 , 25 , 26 ], cost-effectiveness is important to physicians, patients and health insurance institutes [ 7 , 23 , 36 ]. These issues are quite serious for spinal disease, considering the recent increase in the number of cases, high cost of surgery/intervention and maintenance cost after treatment [ 3 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although RCTs that focus on clinical outcomes can provide robust recommendations for spinal clinical practice [ 22 , 23 , 25 , 26 ], cost-effectiveness is important to physicians, patients and health insurance institutes [ 7 , 23 , 36 ]. These issues are quite serious for spinal disease, considering the recent increase in the number of cases, high cost of surgery/intervention and maintenance cost after treatment [ 3 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39] Use of registered health care data for better management Although RCTs that focus on clinical outcomes can provide robust recommendations for spinal clinical practice, 25,26,28,29 cost-effectiveness is important to physicians, patients and health insurance institutes. 26,30,39,40 These issues are quite serious for spinal disease, considering the recent increase in the number of cases, high cost of surgery/intervention and maintenance cost after treatment. 8,39 Because the coverage policy of insurance in uences the practice pattern, safety and cost of spinal surgery, the stakeholders of insurance institutions should know the current utilization of healthcare services.…”
Section: Discussionmentioning
confidence: 99%
“…26,30,39,40 These issues are quite serious for spinal disease, considering the recent increase in the number of cases, high cost of surgery/intervention and maintenance cost after treatment. 8,39 Because the coverage policy of insurance in uences the practice pattern, safety and cost of spinal surgery, the stakeholders of insurance institutions should know the current utilization of healthcare services. 10,41,42 Although those issues have been analyzed by using medical records, the costs varied among societies to obtain a generalized picture of the utilization of medical services.…”
Section: Discussionmentioning
confidence: 99%
“…60 Our group recently published the first health economic analysis of spinal surgery in Brazil. 56 Using data from PRO collected routinely in patients undergoing surgery for lumbar disc herniation, we demonstrated that lumbar discectomy is a very cost-effective treatment for patients with lumbar disc herniation refractory to clinical treatment from private and public health care perspectives. 56 Thus, in addition to serving to evaluate patients' outcomes from their own perspectives, the routine collection of PRO instruments for patients with spinal disorders can be used for health economic analyses.…”
Section: Psychological Aspectsmentioning
confidence: 98%
“…56 Using data from PRO collected routinely in patients undergoing surgery for lumbar disc herniation, we demonstrated that lumbar discectomy is a very cost-effective treatment for patients with lumbar disc herniation refractory to clinical treatment from private and public health care perspectives. 56 Thus, in addition to serving to evaluate patients' outcomes from their own perspectives, the routine collection of PRO instruments for patients with spinal disorders can be used for health economic analyses. We strongly believe that these initiatives are extremely important in the contemporary paradigm of value-based health care, principally in developing countries, where routine assessments of PRO are performed by a very limited proportion of spine care groups.…”
Section: Psychological Aspectsmentioning
confidence: 98%